2020
DOI: 10.1016/j.ajog.2020.03.020
|View full text |Cite
|
Sign up to set email alerts
|

New persistent opioid use after acute opioid prescribing in pregnancy: a nationwide analysis

Abstract: To evaluate the association between opioid prescribing during pregnancy and new persistent opioid use in the year following delivery. MATERIALS AND METHODS: This nationwide retrospective cohort study included patients aged 12À55 years in Optum's deidentified Clinformatics Data Mart Database who were undergoing vaginal delivery or cesarean delivery from 2008 to 2016, with continuous enrollment from 2 years before birth to 1 year postdischarge. Women were included if they were opioid naive in pregnancy (ie, did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(26 reference statements)
3
22
0
Order By: Relevance
“…The exact rate of NPOU is highly dependent on the definition. Our data is consistent with other studies which utilized a similar methodology: Brummett et al NPOU rates between 5.9% to 6.5%; Wright et al 6.8%; Peahl et al 4% 7,16,22 . Not surprisingly, studies with more stringent definitions reported lower rates of NPOU 8,9,23 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The exact rate of NPOU is highly dependent on the definition. Our data is consistent with other studies which utilized a similar methodology: Brummett et al NPOU rates between 5.9% to 6.5%; Wright et al 6.8%; Peahl et al 4% 7,16,22 . Not surprisingly, studies with more stringent definitions reported lower rates of NPOU 8,9,23 .…”
Section: Discussionsupporting
confidence: 93%
“…We were able to demonstrate that several patient characteristics are associated with risk of NPOU among women with perioperative opioid use. We showed that patients who have a mental health diagnosis, have a history of substance use disorder, or high amounts of prescribed OMEs had higher rates of NPOU and these findings are consistent with findings from similar studies 5,9,16,29 . Given our large cohort, the magnitude of these risks is modest and likely merit further confirmation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[4][5][6][7][8][9] Increasing evidence indicates that for both vaginal and cesarean deliveries, opioid prescribing during the postpartum period is associated with an increased risk of SOREs. 5,6,10,11 Approaches that improve postpartum opioid prescribing, including after cesarean, are greatly needed. 12,13 Currently, opioid prescribing guidelines for acute pain among opioid naïve patients recommend the use of the lowest effective opioid dose for the shortest duration.…”
Section: Introductionmentioning
confidence: 99%